Sparse exponential family Principal Component Analysis. (December 2016) - Lu, Meng; Huang, Jianhua Z.; Qian, Xiaoning
Abstract: We propose a Sparse exponential family Principal Component Analysis (SePCA) method suitable for any type of data following exponential family distributions to achieve simultaneous dimension reduction and variable selection for better interpretation of the results. Because of the generality of exponential family distributions, the method can be applied to a wide range of applications, in particular when analyzing high dimensional next-generation sequencing data and genetic mutation data in genomics. The use of sparsity-inducing penalty helps produce sparse principal component loading vectors such that the principal components can focus on informative variables. By using an equivalent dual form of the formulated optimization problem for SePCA, we derive optimal solutions with efficient iterative closed-form updating rules. The results from both simulation experiments and real-world applications have demonstrated the superiority of our SePCA in reconstruction accuracy and computational efficiency over traditional exponential family PCA (ePCA), the existing Sparse PCA (SPCA) and Sparse Logistic PCA (SLPCA) algorithms. Abstract : Highlights: A Sparse exponential family Principal Component Analysis is proposed. It has wide applications to any data following exponential family distributions. Efficient solutions can be achieved with closed-form update rules. The performance is enhanced with appropriate assumption of the data distribution. This model is flexible and highly extensible.